TINJAUAN YURIDIS TERHADAP HUBUNGAN HUKUM KARENA WANPRESTASI DI DALAM HUTANG PIUTANG (Studi Putusan Pengadilan Negeri Lubuk Pakam No.05/Pdt.G/2007/PN.LP) - Taufik Siregar; Isnaini Isnaini; Jadrias Tarigan (Jurnal Ilmiah Penegakan Hukum, 2014)
Settlement of legal disputes due to additional defaults in the agreementcan be made payable litigation and non litigation. In litigation can be donepremises ways filed to a local court. While non litigation conducted by outsidecourt as mediation, arbitration, peace, etc.